Analisis Semiotika Pesan Moral dalam Bungkus Rokok - Dwi Putra, Muhammad Cahfri Eza; Putra, Dhanu Ario; Rullyanti, Merry (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This research investigates the semiotic elements and moral messages embedded in the images found on cigarette packs, specifically focusing on the types of sign-meanings (denotation, connotation, and myth) and their moral implications. Data were collected from 10 different cigarette packs and analyzed using Roland Barthes' semiotic theory The analysis reveals that all 10 packs contain denotation and connotation, while 8 packs also exhibit myth. Beyond these semiotic analyses, the research uncovers significant moral messages conveyed through the warning images. These pictures serve as stark reminders of the severe health consequences of smoking, prompting reflection on the ethical implications of tobacco consumption. They underscore the importance of informed decision-making and challenge the normalization of smoking within cultural contexts. In conclusion, the semiotic and moral analysis of cigarette pack images reveals a complex interplay between visual elements and societal perceptions. The findings highlight the dual role of these images in conveying direct health warnings and broader ethical considerations, ultimately advocating for a more informed and health-conscious society.